Introduction to programming: Portrait of Higher Education in computer science in Portugal - Sobral, Sónia Rolland (2019)
The first contact with computational thinking and programming languages of students entering higher education in computer science courses is extremely important for the professional future of these students: if successful it may indicate a promising career; otherwise it often leads to early abandonment of these students. The creation and maintenance of courses (1st cycle and 1st plus 2nd cycle integration) in information technology worries directors, coordinators and teachers of these courses. The area is in constant development and, despite the need for highly specialized technicians and almost zero unemployment, that it does not attract as much students who finish high school as it could. We found 193 courses in computer science in Portuguese higher education. Of these we have 106 1st Cycles, 15 Integrated and 1 Preparation; 66 different institutions. We study these courses: type of education (public or private), denomination of courses and types (1st cycle, integrated master's degree or preparation). 59 are public education courses: those in private education do not have much information on the internet. Of these 59 courses only 46 have information available online. This article belongs to an investigation that is done around the university courses of computer science: a picture of what exists, which are the vacancies, averages, success rates, how computer science and programming are linked in curricular terms, or in terms of curricular units and in terms of programming languages. This article focuses on the initial year and initial curricular units of programming of ten Portuguese computer courses that were considered more significant: programming languages, objectives, bibliography and type of evaluation. It is very important to study what is being done and how it is done.